Studi Naratif Relawan Dalam Penanganan Orang Dengan Gangguan Jiwa Berbasis Komunikasi Terapeutik - Shalisha Karmann Ghia Roosmartono; Bani Eka Dartiningsih; Sri Wahyuningsih (Jurnal Khabar: Komunikasi dan Penyiaran Islam, 2025)
This study aims to analyze therapeutic communication practices employed by volunteers in community-based care for people with mental disorders (ODGJ). The focus of the research is directed at the meaning, communication strategies, and challenges faced by volunteers in the mentoring process. This study used a qualitative approach with a narrative study method. Data were obtained through in depth interviews with volunteers directly involved in mentoring people with mental disorders. Data were analyzed by tracing the informants' narrative flow to identify key themes in therapeutic communication practices, which were then interpreted using a therapeutic communication theoretical framework. The results indicate that volunteers' therapeutic communication is adaptive and contextual, not tied to formal clinical procedures. Volunteers interpret therapeutic communication as a process of building a sense of safety and empathetic relationships, especially in crisis situations. These communication practices involve strategic flexibility, the use of nonverbal communication, and the communicator's emotional regulation. These findings confirm that volunteers play a strategic role as therapeutic communication actors in community-based mental health services. This research contributes to the development of therapeutic communication studies by expanding its application beyond formal professional settings.